Answer:
The equation of the given graph is:
![y=-(x-3)^2+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cjlf4d90z1n6w7j69oa3ux6tf51pnljlfe.png)
Explanation:
We know that the general equation of a downward parabola with vertex at (h,k) is given by the formula:
![y=a(x-h)^2+k](https://img.qammunity.org/2020/formulas/mathematics/high-school/7xiq973pej7bis77rj649g420rebwvc4wx.png)
where a<0
Here in each of the options we have a= 1 or -1
but as a has to be less than 1 this means that a= -1
Also, we have: (h,k)= (3,1)
i.e. h=3 and k=1
Hence, putting the values of h,k and a in the general equation we get:
Hence, the equation of parabola is:
![y=-(x-3)^2+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cjlf4d90z1n6w7j69oa3ux6tf51pnljlfe.png)